THE EFFECTS OF ELEMENTARY STUDENTS’COMPREHENSION OF ENGLISH VOCABULARY WHEN USING GADGETS - Melda Mahniza; Elviza Yeni Putri; Nurul Inayah Hutasuhut (Ensiklopedia of Journal, 2023)
This research is entitled The Effects of Elementary  Students' Comprehension of English Vocabulary When Using Gadgets. This research analyzes the positive and negative effects of elementary students' English vocabulary comprehension when using gadgets. Second language acquisition theory is used to classify the data. The methods used in this research are descriptive-qualitative and observational. The data for this research is the English vocabulary contained in four gadgets and images contained in game applications that use English. The data source is four elementary school students from Karya Sukadamai Street, Sei Agul District, Medan, playing English games on their gadgets. The research found that gadget use has two positive and negative effects on elementary school students' understanding of English vocabulary. It has also been shown that elementary school students unconsciously acquire English vocabulary through learning, as explained in the first hypothesis of Stephen Krashen's theory of second language acquisition.Keywords: Elementary students , English vocabulary, Gadgets, Second language acquisition.